Small Area Estimation Of Expenditure Per-capita in Banyuwangi with Hierarchical Bayesian and Empirical Bayes Methods - Wirajaya Kusuma; Nur Iriawan; Irhamah Irhamah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
One of the economic indicators that are widely used to measure the level of prosperity and welfare is per capita income. However, an accurate income data is difficult to be obtained. In Susenas this data is approached by using data on expenditures per capita. This study employ Hierarchical Bayes (HB) and Empirical Bayes (EB) methods to be applied to Small Area Estimation (SAE) to estimate the expenditure per-capita in Banyuwangi. The results showed indirect estimation using hierarchical Bayes and Empirical Bayes produce RMSE values smaller than the direct estimation. The HB method, on the other hand, produces smaller RMSE value than the EB method. Finally, this research suggests to use HB method to estimate the expenditure per-capita in Banyuwangi rather than direct estimation which is used nowadays.